The Effect of The Touché Therapy On The Anthropometry for Infants In Working Area Service of The PublicHealthCenterPesantren I Kediri. - Heny Kristanto (Akademi Keperawatan Dharma Husada Kediri, 2016)
The hindrance of infant development is caused by unbearable environmental factor. From year to year, it has been recorded that the infant natal figure is still high, including the natal figure in Kediri – City. Since the high infant natal figure and the infant age as the potential period for development, therefore, it should be optimally cared the development for infant, one of them is done by touché therapy. The objective of the research is to prove that there is a difference between infant cared with anthropometry therapy using touché therapy in working area service of the Public Health Center Pesantren I Kediri. The research plan uses the Randomized Control Trial, the collecting sampling technique uses Total Sampling, and the total sample is 20 infant. Variable research is touché therapy (independent variable) and infant anthropometry (variable dependent). From the result of processing data of anthropometry by using ANOVA test and T test on dependent sample, it can be obtained the significant improvement on the height of the infant (for the treatment group on the 4th week observation, the control group on the 5th week observation and the control group on the 6th week observation). No significant improvement for the head circle of the infant for the treatment control group. The significant improvement on the height is caused by the secretion of Neuro-chemical beta-endorphin the result of the touché therapy treatment, and later it can cause the discretion of hormonal development. The significant improvement on the weight is caused by the stimulus of the nervous vagus that can increase the level of gastric and insulin absorption enzyme. No significant improvement on the head circle of the infantfor the treatment and control groups is caused by the very slow development of the brain cell. key words: Touché therapy, Anthropometry